INSTRUMEN PENILAIAN SIKAP SOSIAL (Studi Penilaian Sikap Sosial pada mata pelajaran Fikih di Jurusan Tehnik dan Bisnis Sepeda Motor SMK Muhammadiyah 1 Patuk) - Baidhowi, Muhammad Rizal (Edudeena : Journal of Islamic Religious Education, 2018)
Abstract: Sisdiknas 20/2003, law No. 20 of 2003 describes the purpose of national education is to the development of potential learners in order to become a man of faith and piety to God Almighty, precious, healthy, have learned, accomplished, creative, independently, and become citizens of a democratic and accountable. Expressed that the national education goals is achieved through a number of competencies in order to be human Indonesia expected. These goals are also very comprehensive summed up into the competency-specific competency. In the curriculum, there is 2013 KI KI 1 and 2 containing the competence of attitude, which is divided into an attitude of spiritual and social attitudes. Presence of KI KI 1 and 2 are expected to realize the goal of the comprehensive education to understand KI 1 and KI2 2013 in the curriculum of course we will look at different ideas with KTSP 2006. Another thing is also found in his system. With the goal of a comprehensive, certainly in the assessment also requires a comprehensive assessment as well as authentic. Abstrak: Sisdiknas 20/2003, UU No. 20 Tahun 2003 tentang menjelaskan tujuan pendidikan nasional adalah untuk berkembangnya potensi peserta didik agar menjadi manusia yang beriman dan bertakwa kepada Tuhan Yang Maha Esa, berakhlak mulia, sehat, berilmu, cakap, kreatif, mandiri, dan menjadi warga negara yang demokratis serta bertanggung jawab. Tersurat bahwa tujuan pendidikan nasional tersebut dicapai melalui sejumlah kompetensi agar menjadi manusia Indonesia yang diharapkan. Tujuan tersebut juga sangat komprehensif yang disimpulkan ke dalam kompetensi-kompetensi tertentu. Dalam kurikulum 2013 terdapat KI 1 dan KI 2 yang berisi kompetensi sikap, yang terbagi atas sikap spiritual dan sikap sosial. Hadirnya KI 1 dan KI 2 diharapkan mampu mewujudkan tujuan pendidikan yang komprehensif tersebut Memahami KI 1 dan KI2 pada Kurikulum 2013 tentu kita akan melihat pemikiran yang berbeda dengan KTSP 2006. Hal lain juga ditemui dalam sistem penilaiannya. Dengan tujuan yang komprehensif, tentu dalam penilaian juga membutuhkan penilaian yang komprehensif serta aoutentik.